The ongoing range expansion of the invasive oak lace bug across Europe: current occurrence and potential distribution under climate change - Albert Ciceu; Flavius Bălăcenoiu; Maarten de Groot; Debojyoti Chakraborty; Dimitrios Avtzis; Marek Barta; Simon Blaser; Matteo Bracalini; Bastien Castagneyrol; Ulyana A. Chernova; Ejup Çota; György Csóka; et al. (Science of The Total Environment, 2024)

Tournament ABC analysis of the western Palaearctic population history of an oak gall wasp, Synergus umbraculus - Graham N. Stone; Sarah C. White; György Csóka; George Melika; Serap Mutun; Zsolt Pénzes; S. Ebrahim Sadeghi; Karsten Schönrogge; Majid Tavakoli; James A. Nicholls (Molecular Ecology, 2017)
Approximate Bayesian computation ( ABC ) is a powerful and widely used approach in inference of population history. However, the computational effort required to discriminate among alternative historical scenarios often limits the set that is compared to those considered more likely a priori. While often justifiable, this approach will fail to consider unexpected but well‐supported population histories. We used a hierarchical tournament approach, in which subsets of scenarios are compared in a first round of ABC analyses and the winners are compared in a second analysis, to reconstruct the population history of an oak gall wasp, Synergus umbraculus (Hymenoptera, Cynipidae) across the Western Palaearctic. We used 4,233 bp of sequence data across seven loci to explore the relationships between four putative Pleistocene refuge populations in Iberia, Italy, the Balkans and Western Asia. We compared support for 148 alternative scenarios in eight pools, each pool comprising all possible rearrangements of four populations over a given topology of relationships, with or without founding of one population by admixture and with or without an unsampled “ghost” population. We found very little support for the directional “out of the east” scenario previously inferred for other gall wasp community members. Instead, the best‐supported models identified Iberia as the first‐regional population to diverge from the others in the late Pleistocene, followed by divergence between the Balkans and Western Asia, and founding of the Italian population through late Pleistocene admixture from Iberia and the Balkans. We compare these results with what is known for other members of the oak gall community, and consider the strengths and weaknesses of using a tournament approach to explore phylogeographic model space.

Mitochondrial barcodes are diagnostic of shared refugia but not species in hybridizing oak gallwasps - JAMES A. NICHOLLS; RICHARD J. CHALLIS; SERAP MUTUN; GRAHAM N. STONE (Molecular Ecology, 2012)
Mitochondrial DNA barcodes provide a simple taxonomic tool for systematic and ecological research, with particular benefit for poorly studied or species‐rich taxa. Barcoding assumes genetic diversity follows species boundaries; however, many processes disrupt species‐level monophyly of barcodes leading to incorrect classifications. Spatial population structure, particularly when shared across closely related and potentially hybridizing taxa, can invalidate barcoding approaches yet few data exist to examine its impacts. We test how shared population structure across hybridizing species impacts upon mitochondrial barcodes by sequencing the cytochrome b gene for 518 individuals of four well‐delimited Western Palaearctic gallwasp species within the Andricus quercuscalicis species group. Mitochondrial barcodes clustered individuals into mixed‐species clades corresponding to refugia, with no difference in within‐ and between‐species divergence. Four nuclear genes were also sequenced from 4 to 11 individuals per refugial population of each species. Multi‐locus analyses of these data supported established species, with no support for the refugial clustering across species seen in mitochondrial barcodes. This pattern is consistent with mitochondrial introgression among populations of species sharing the same glacial refugium, such that mitochondrial barcodes identify a shared history of population structure rather than species. Many taxa show phylogeographic structure across glacial refugia, suggesting that mitochondrial barcoding may fail when applied to other sets of co‐distributed, closely related species. Robust barcoding approaches must sample extensively across population structure to disentangle spatial from species‐level variation. Methods incorporating multiple unlinked loci are also essential to accommodate coalescent variation among genes and provide power to resolve recently diverged species.

Corythucha ciliata, a new Platanus pest in Turkey - Serap Mutun (Phytoparasitica, 2009)

The phylogeographical clade trade: tracing the impact of human‐mediated dispersal on the colonization of northern Europe by the oak gallwasp Andricus kollari - GRAHAM N. STONE; RICHARD J. CHALLIS; RACHEL J. ATKINSON; GYÖRGY CSÓKA; ALEX HAYWARD; GEORGE MELIKA; SERAP MUTUN; SONJA PREUSS; ANTONIS ROKAS; EBRAHIM SADEGHI; KARSTEN SCHÖNROGGE (Molecular Ecology, 2007)
Human dispersal of organisms is an important process modifying natural patterns of biodiversity. Such dispersal generates new patterns of genetic diversity that overlie natural phylogeographical signatures, allowing discrimination between alternative dispersal mechanisms. Here we use allele frequency and DNA sequence data to distinguish between alternative scenarios (unassisted range expansion and long range introduction) for the colonization of northern Europe by an oak‐feeding gallwasp, Andricus kollari . Native to Mediterranean latitudes from Portugal to Iran, this species became established in northern Europe following human introduction of a host plant, the Turkey oak Quercus cerris . Colonization of northern Europe is possible through three alternative routes: (i) unassisted range expansion from natural populations in the Iberian Peninsula; (ii) unassisted range expansion from natural populations in Italy and Hungary; or (iii) descent from populations imported to the UK as trade goods from the eastern Mediterranean in the 1830s. We show that while populations in France were colonized from sources in Italy and Hungary, populations in the UK and neighbouring parts of coastal northern Europe encompass allozyme and sequence variation absent from the known native range. Further, these populations show demographic signatures expected for large stable populations, rather than signatures of rapid population growth from small numbers of founders. The extent and spatial distribution of genetic diversity in the UK suggests that these A. kollari populations are derived from introductions of large numbers of individuals from each of two genetically divergent centres of diversity in the eastern Mediterranean. The strong spatial patterning in genetic diversity observed between different regions of northern Europe, and between sites in the UK, is compatible with leptokurtic models of population establishment.

Longitudinal range expansion and cryptic eastern species in the western Palaearctic oak gallwasp, Andricus coriarius - RICHARD J. CHALLIS; SERAP MUTUN; JOSE‐LUIS NIEVES‐ALDREY; SONJA PREUSS; ANTONIS ROKAS; ALEXANDRE AEBI; EBRAHIM SADEGHI; MAJID TAVAKOLI; GRAHAM N. STONE (Molecular Ecology, 2007)
The oak gallwasp Andricus coriarius is distributed across the Western Palaearctic from Morocco to Iran. It belongs to a clade of host‐alternating Andricus species that requires host oaks in two sections of Quercus subgenus Quercus to complete its lifecycle, a requirement that has restricted the historic distribution and dispersal of members of this clade. Here we present nuclear and mitochondrial sequence evidence from the entire geographic range of A. coriarius to investigate the genetic legacy of longitudinal range expansion. We show A. coriarius as currently understood to be para‐ or polyphyletic, with three evolutionarily independent (but partially sympatric) lineages that diverged c. 10 million years ago (mya). The similarities in gall structure that have justified recognition of single species to date thus represent either strong conservation of an ancestral state or striking convergence. All three lineages originated in areas to the east of Europe, underlining the significance of Turkey, Iran and the Levant as ‘cradles’ of gallwasp evolution. One of the three lineages gave rise to all European populations, and range expansion from a putative Eastern origin to the present distribution is predicted to have occurred around 1.6 mya.